Method of calculating the pressure on the soil of wheeled tractors - V. Yu. Revenko; A. N. Nazarov; V. I. Skorlyakov (Аграрная наука Евро-Северо-Востока)
The market of tractors in Russia has changed greatly in recent years. A number of new suppliers have appeared on the market, abandoned brands are replaced for Russian analogues and machines from friendly countries. It is hard to evaluate all the quantitative and qualitative diversity of tractors provided to agricultural producers through the system of machine tests, especially considering that every manufacturer has a large number of standard size ranges of power equipment. Nevertheless, the customer should have access to information about the basic consumer properties and the degree of effectiveness of a particular machine unit. The article provides a computational method for evaluating one of the most important functional indicators of tractors, namely, the level of impact of its wheels on the soil, using limited initial information: technical characteristics and operational documentation of the manufacturer. The algorithm given in the text was approved during testing real tractor samples. Insignificant differences in the assessment of the maximum pressure on the soil, obtained as a result of measurements and calculations (the difference is 1.9-3.3 %) indicate a high degree of reliability of the developed methodology, as well as the possibility of its application in engineering practice to evaluate the functional indicators of tractors, including taking into account changes in their size and mass parameters when equipped with ballast weights, agricultural machines, implements, dual tires, etc. To make calculations, it is enough to know the weight of the tractor, the weight of ballast loads (mounted implements), the size of the installed tires, their static radius and the amount of tire inflation pressure. The methodology will significantly improve the quality of the predictive assessment of the level of impact on the soil of both mass-produced and designed tractor equipment.